Viewing The Achievement of The Covid-19 Vaccination in Indonesia From A Human Development And Urbanization Perspective - Abdurrahman; Erwin Tanur (Jurnal Kebijakan Pembangunan, 2022)
The disparity in the achievement of Covid-19 vaccination among provinces in Indonesia is still quite high. This can be one reason why the number of Covid-19 patients is still fluctuating even today. Nevertheless, the Covid-19 vaccine is still very useful to reduce Covid-19 infection. This study aims to see whether Human Development Index (HDI) and urbanization rate are the reasons behind the achievement of Covid-19 vaccination in Indonesia. The research used a quantitative approach with a cross-sectional research design. The data used are secondary data from BPS and the Ministry of Health. The data were analyzed using tabulations, graphs, and inferential analysis through the Pearson correlation test and multiple linear regression. The results show that about three-quarters of provinces in Indonesia are still below the Covid-19 vaccination target to achieve herd immunity. The scatter plot graph shows provinces with relatively low vaccination rates, having relatively low HDI and urbanization levels. Vice versa. Meanwhile, the results of a multiple linear regression analysis found that HDI and the level of urbanization had a very strong and statistically significant effect on the achievement of Covid-19 vaccination in all provinces in Indonesia. These results conclude that the achievement of the Covid-19 vaccination in Indonesia is the background for the achievement of the Covid-19 vaccination in Indonesia. Therefore, provinces with low Covid-19 vaccination achievements can be encouraged to continue pursuing the herd immunity target by paying attention to the characteristics of provinces with high HDI and high urbanization. Abstrak Disparitas capaian vaksinasi Covid-19 antarprovinsi di Indonesia masih cukup tinggi. Hal ini bisa menjadi salah satu alasan mengapa jumlah pasien Covid-19 masih fluktuatif bahkan hingga saat ini. Meski demikian, vaksin Covid-19 tetap sangat bermanfaat untuk mengurangi infeksi Covid-19. Penelitian ini bertujuan untuk melihat apakah Indeks Pembangunan Manusia (IPM) dan tingkat urbanisasi melatarbelakangi capaian vaksinasi Covid-19 di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan desain penelitian secara cross section. Data yang digunakan merupakan data sekunder dari BPS dan Kementrian Kesehatan. Data tersebut dianalisis menggunakan tabulasi, grafik, dan analisis inferensial melalui uji korelasi Pearson dan regresi linier berganda. Hasil penelitian menunjukkan bahwa sekitar tiga perempat provinsi di Indonesia masih di bawah target vaksinasi Covid-19 untuk mencapai herd immunity. Grafik scatter plot menunjukkan provinsi dengan capaian vaksinasi yang relatif rendah, memiliki IPM dan tingkat urbanisasi yang juga relatif rendah. Begitu pula sebaliknya. Sedangkan hasil dari analisis regresi linear sederhana menemukan bahwa IPM dan tingkat urbanisasi mempunyai pengaruh cukup kuat dan signifikan secara statistik terhadap capaian vaksinasi Covid-19 di seluruh provinsi di Indonesia. Hasil ini memberikan kesimpulan bahwa capaian vaksinasi Covid-19 di Indonesia melatarbelakangi capaian vaksinasi Covid-19 di Indonesia. Oleh karena itu Provinsi yang capaian vaksinasi Covid-19 yang masih rendah, dapat didorong untuk terus mengejar target herd immunity dengan memperhatikan bagaimana karakteristik provinsi dengan IPM dan urbanisasi tinggi.